"Take it personally" - Sapru, Jyoti (Teorija in praksa, 2016)
The article speaks about the introduction of the life course approach and auto/biographical method to the study of sociology in Slovenia and in India. It explores the method's potential for researching issues of social change over time in general and issues of sexuality and reproduction in particular. The authors claim that bringing the personal into social analysis enables a better understanding of the social conditioning of reproduction as well as the subtle strategies and coping mechanisms that women from three generations in the samples in Slovenia and in India used in order to react to both the social norms and hidden messages regarding reproductive choices.
Keywords: Družbene spremembe; India; Indija; Reproduction; Reprodukcija; sexual intercourse; Sexuality; Slovenia; Slovenija; Social change; Sociologija vsakdanjega življenja; Sociology of everyday life; Spolnost; woman; Women; Ženske